A critical analysis of development indices - Abdul Aziz, SumayyaH; Mohd Amin, Ruzita (2014)
Historically, Gross National Product (GNP) has been thought of as a key indicator in measuring the development level of a nation. Over the years, researchers have found that the single GNP indicator is not sufficient to be used to measure development. Numerous efforts have been done to create other composite indicators that could serve as complements or alternatives to the traditional measure. The questions that arise from these efforts include: (i) What are the development frameworks that underlie the existing development indices? (ii) What are the advantages and limitations of the particular development indices? This study attempts to address the two questions by providing an overview of the existing indices and their evolution over the years, and categorize these indices based on the various development frameworks. The study also aims to identify the advantages and limitations of the existing development indices, and to recommend the direction towards developing indices which are more integrated, holistic and comprehensive in nature. A systematic review of related literature, works, and papers in books, journals, reports, and conferences, were undertaken using meta analysis and content analysis methods. The findings of this study reveal that in general, most of the existing development indices have been criticized with regard to poor data, incorrect choice of indicators, involvement of only a few dimensions of the broader concept of development, lack of consideration on non-material aspects and poor specification of the development framework. Therefore, a comprehensive development index needs to be developed to measure a more holistic approach of development.